Sekolah Islam Asal Usul dan Pertumbuhanya : Kontribusi Sekolah Islam Terpadu dalam Pembentukan Generasi Qur’ani - Hamzah Irfanda; Iswantir Iswantir; Salmiwati Salmiwati (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This study examines the role of Integrated Islamic Schools (SIT) in the formation of the Qur'anic generation in Indonesia, with a special focus on the Ar-Risalah boarding school as a case study. SIT, which integrates general education and Islamic religion, has been an important educational model since the late 1980s, although its roots date back to the early 20th century in various Islamic institutions in Indonesia. This study uses a qualitative approach with field methods to understand how Ar-Risalah boarding schools contribute to forming students with strong Qur'anic values. This study uses a qualitative method. Data in this study were obtained by referring to existing literature in books, journals, questionnaires or interviews. The results of the study indicate that SIT, through programs such as memorizing the Qur'an and strengthening spiritual values, plays a significant role in shaping students' characters. However, challenges still exist in the internalization of Qur'anic values ​​and the application of adab towards the Qur'an, with data showing that only a portion of students truly understand and practice these values. This study emphasizes the importance of innovation in more applicable teaching methods and parental involvement and a supportive school environment in increasing the effectiveness of Qur'anic generation education.